Determining The Black-Box Component's Failure. - Hilal, Ibrahim; Jantan, Aman (2007)
Many papers propose different approaches to evaluate the reliability of black-box components based on component's success. This paper determines or evaluates component's reliability based on its failure. Since even reliable components might fail, we argue that component's acquirer should evaluate the component's reliability based on its failure and not on its success- In this paper we propose a new approach towards determining the component's failure. Both the operational profile and the appropriate test cases are needed to support our approach.